THEORIES ON LABOR SOCIOLOGY AND THE IMPORTANCE OF THEIR POSITIVE ASPECTS IN THE RATIONAL ORGANIZATION OF THE LABOR PROCESS - Nuriddin N. Rakhmatov, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
In the global economic system, raw materials, production, goods, trade and mutually stable continuous financial relations suddenly undergo major changes, breaking the communication chains of the economies of countries and states that have been strengthened for many years. Any countries that pay great attention to the maintenance of labor stability in production and enterprises and organizations living in the midst of such global changes and economic measures are taking measures to adapt and stabilize their internal and external socio-economic policies to the changing environment.